Promotion vs. Education in Choosing “Real Food” - Cachelin, Adrienne; Schott, Willem (Consilience, 2017)
The global agro-industrial system contributes to an abundance of human and ecological health problems from social injustices and public health issues to global warming and ecological degradation. In response to these problems, universities across the country are joining the Real Food Challenge (RFC). The RFC is a national student-driven organization that defines “Real Food” as possessing at least one of the following four attributes: local, fair, ecologically-sound, and/or humane. By mobilizing the power of students on college campuses, the RFC aspires to shift up to one billion dollars in dining purchasing towards “Real Food” by the year 2020. One key element for the continued success of the RFC is a better understanding of factors affecting college student food choice. Our research explores these factors as well as the types of interventions that will most effectively impact them. Both educational and social marketing strategies were found to effectively increase the importance of Real Food factors affecting college student food choice decisions. In addition, the overwhelming majority of student participants believe that their personal food choices can have an impact on moving the larger industrial food system towards sustainability. Identifying strategies that encourage students to choose more “Real Food” can provide administrations with the necessary support to increase sustainable food purchasing while fueling the RFC on its industry-shifting path towards a more sustainable food system overall.